2018
DOI: 10.1007/s10916-018-1015-5
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Improve Start Time in the Operating Theatre: a Systematic Review

Abstract: Operating theatres represent a significant cost burden for healthcare providers around the world. Theatre start time is widely acknowledged as an important target for efficiency savings. However, there is uncertainty surrounding the effectiveness of strategies to improve start time, and questions regarding the barriers to their implementation. We conducted a systematic review of bibliographic databases to identify primary research papers assessing the effect of interventions on theatre start time. Two hundred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 24 publications
0
19
0
4
Order By: Relevance
“…Lean Six Sigma also provides useful frameworks to help hospital staff identify causes of delays in their own institutions. 113 This combination outperforms the use of only one other methodology; however, this combination tends to be composed of larger, private hospitals with more resources for quality improvement. 114 Our review also found that most of the studies mapped their activities to describe and understand flows and patient care processes; to this end, healthcare organizations mainly relied on value stream mapping, thereby being the most important tool in LH.…”
Section: Discussionmentioning
confidence: 99%
“…Lean Six Sigma also provides useful frameworks to help hospital staff identify causes of delays in their own institutions. 113 This combination outperforms the use of only one other methodology; however, this combination tends to be composed of larger, private hospitals with more resources for quality improvement. 114 Our review also found that most of the studies mapped their activities to describe and understand flows and patient care processes; to this end, healthcare organizations mainly relied on value stream mapping, thereby being the most important tool in LH.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, both methodologies complement each other. Lean-six sigma also provides useful frameworks to help hospital staff identify causes of delays in their own institutions [ 155 ]. This combination outperforms the use of only one methodology.…”
Section: Discussionmentioning
confidence: 99%
“…Sykehus organiseres og driftes ulikt (Halim, Khan & Ali, 2018). Selv om ikke all kunnskap fra forskning på forsinkelser har direkte overføringsverdi til eget sykehus, kan det vaere mye å hente fra andre studier, ikke minst kunnskap om effektiv drift av operasjonsenheter og hva en kan gjøre for å redusere forsinkelser (Healey et al, 2015a;Healey, El-Othmani, Healey, Peterson & Saleh, 2015b;Charlesworth & Pandit, 2020).…”
Section: Hva Var De Egentlige åRsaker Til Forsinkelser Ved Elektive Operasjonerunclassified
“…Kartlegging av årsaker gir allikevel god grunn til å anta at planlegging og gjennomføring av elektive operasjoner kan forbedres gjennom enkle grep. I en studie blir begrepet «gullpasient» brukt som et godt tiltak for å redusere forsinkelser hos tidligpasienten (Halim et al, 2018). «Gullpasient» er en pasient som med liten sannsynlighet vil oppleve forsinkelser på grunn av at alle nødvendige preforberedelser er gjennomført.…”
Section: Behov For Forbedringunclassified